Psychoeducation Posters and Leaflets Effects to Improve Inclusive Education Awareness of Parents with Typically Developing Children (TDC) in Indonesia - Tarnoto, Nissa; Pranungsari, Dessy; Aulia, Aulia (Universitas PGRI Yogyakarta, 2025)
One of the most persistent challenges in supporting children with Special Educational Needs (SEN) is the level of awareness and acceptance among parents of Typically Developing Children (TDC). Limited understanding of inclusive education often contributes to stigma, resistance, and reduced collaboration between schools and families. This study examined the effectiveness of psychoeducational posters and leaflets in improving TDC parents’ comprehension of inclusive education. Using a quasi-experimental pre–post design, fourteen TDC parents participated and completed the Inclusive Education Comprehension Questionnaire. Data were analyzed using the Wilcoxon test due to the small sample size and non-parametric distribution. Results showed a statistically significant increase in parents’ understanding after receiving psychoeducation materials. Parents reported clearer knowledge about the purpose, benefits, and implementation of inclusive education, indicating that visually delivered, indirect psychoeducation remains effective even in the digital era. These findings suggest that poster- and leaflet-based psychoeducation can serve as a practical and scalable strategy for schools and educators to promote greater acceptance toward children with SEN. However, to achieve more sustainable, more profound behavioral change, future interventions should combine indirect media with direct psychoeducational activities, such as workshops or guided discussions, particularly for parents with limited reading motivation or literacy challenges. Keywords: children with special educational needs (SEN), inclusive education, leaflets, posters, parents with typically development children (TDC), psychoeducation